DEVELOPMENT OF NOVEL MUSCLE-SPECIFIC ADENO-ASSOCIATED VIRAL VECTOR CONSTRUCTS FOR GENE THERAPY OF DUCHENNE MUSCULAR DYSTROPHY - Brenda Rasowo; Sarcar Shilpita; Samara Ermira; Marinee Chuah; Thierry Vanden Driessche (European Scientific Journal, ESJ, 2014)
To investigate efficacy of synthetic SPc5-12 promoter expression in skeletal and heart muscles and compare its activity with that of MYODI and MYLK2 muscle specific promoters. We hypothesized that we could achieve efficient, safe and global cardiac and muscle gene transfer in mice following a single intravenous injection of scAAV-SPc5-12-luc2 vector. We reported relatively robust levels of luciferase expression in the heart and moderate levels in the skeletal muscles in particular the tibialis and gastrocnemius which are representative of fast twitch muscle fibers. No significant luciferase expression was observed in other tissues such as liver, lung, spleen and brain. The result of the luciferase expression quantified as (photons/sec/cm2/steridian) in the individual dissected organs were similar to the optical imaging results observed of the whole mice. This study report for the first time that the SPc5-12 promoter delivered by AAV9 serotype is robust and muscle specific.